Systematic review of nanoelectronic drug delivery systems advancing technological innovation, clinical integration, and personalized therapy - Eze, Val Hyginus Udoka; Eze, Chidinma Esther; Alaneme, George Uwadiegwu; Mirembe, Nansamba Fridah; Ugwu, Okechukwu Paul-Chima; Ogenyi, Fabian C.; Ugwu, Chinyere Nneoma; Okon, Michael Ben; Ugwu, Jovita Nnenna (Frontiers in Nanotechnology, 2026)
Nanoelectronic Drug Delivery Systems (NEDDS) represent a transformative convergence of nanotechnology, electronic engineering, and precision medicine. This systematic review critically evaluates the evolution, technological advancements, clinical applications, and prospects of NEDDS in personalized therapy. Guided by the PRISMA framework, a comprehensive synthesis of 135 high-quality, peer-reviewed studies was conducted, incorporating robust quality appraisal using CASP and a modified JBI checklist. Thematic analysis via NVivo identified four central domains: historical development, technological innovation, clinical integration, and safety-regulatory considerations. Key findings reveal that NEDDS enable precision targeting through functionalized carriers, real-time therapeutic monitoring, and dynamic treatment adjustment based on pharmacogenomic data, thereby enhancing efficacy and minimizing adverse effects. Specific applications include implantable nanosensors for continuous glucose monitoring in diabetes management, electroresponsive carriers for on-demand chemotherapy delivery in oncology, and transdermal nanochips for pain modulation. Recent advancements such as AI-driven drug dosing algorithms, wireless feedback-controlled microdevices, and integration with 3D-printed personalized drug reservoirs highlight the growing sophistication of NEDDS. These systems also leverage smart technologies to enhance patient compliance and therapeutic autonomy. Despite these innovations, challenges persist, particularly concerning nanomaterial biocompatibility, ethical data governance, and underdeveloped regulatory infrastructure. The review underscores the urgent need for comprehensive safety evaluations, interdisciplinary collaboration, and streamlined regulatory frameworks to facilitate clinical translation. With strategic innovation and oversight, NEDDS holds immense potential to redefine personalized healthcare by delivering smarter, safer, and more adaptive treatment modalities.